Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Divisi Steel pada PT. Tira Austenite Tbk Cabang Pulogadung - Rahma Fitriani; Imelda Sari; Angestika Wilandari (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
PT. Tira Austenite Tbk is one of the leading Trade Industry in Indonesia. Required to have good employees in accordance with the desired qualifications in order to improve company performance and be ready to face increasingly rapid industrial competition. Company leaders must motivate employees to have high discipline in order to achieve company goals. This study aims to determine the effect of leadership style (X1) on employee performance (Y), to determine the effect of work discipline (X2) on employee performance (Y). as well as knowing the effect of leadership style and work discipline on employee performance. This study used a quantitative method with a questionnaire distribution technique to obtain primary data from employees of the Steel Division of PT. Tira Austenite Tbk Pulogadung Branch. The sample of this research is 50 employees using saturated sampling technique. The results of this study found that the Leadership Style variable (X1) has a significant and positive effect on performance (Y) with a tcount value of 4.122 > ttable of 2.011 and a significant value of 0.00 <0.05. Work Discipline Variable (X2) has no significant and negative effect on Employee Performance (Y) with a tcount value of -0.889 < ttable of 2.011 and a significant value of 0.379 > 0.05. Leadership Style (X1) and Performance Discipline (X2) simultaneously influence Employee Performance (Y) in the steel division at PT.Tira Austenite Tbk Pulogadung branch.